3D Printing of Carbon Nanotube (CNT)/Thermoplastic Polyurethane (TPU) Functional Composites and Preparation of Highly Sensitive, Wide‐range Detectable, and Flexible Capacitive Sensor Dielectric Layers via Fused Deposition Modeling (FDM). Issue 7 (29th January 2023) - Yang, Leipeng; Liu, Xin; Xiao, Yuan; Zhang, Yongyan; Zhang, Gaiping; Wang, Yuping
Abstract: As one of the widely used additive manufacturing technologies, FDM has been limited by small variety of available materials, poor mechanical properties, and lack of functionality of the FDM‐printed parts. In this study, CNT/TPU filaments are prepared, and their thermal behavior is determined to lay the foundation for FDM process. The effects of the CNT content on the mechanical and conductivity properties of FDM‐printed samples are investigated, and the FDM‐printed CNT/TPU dielectric layers are explored for capacitive sensing applications. The results show that the incorporation of CNT significantly affects their mechanical, electrical, and capacitive sensing properties. The addition of 6 wt.% CNT increases the tensile strength by 199%, the flexural strength by 34%, and the electrical resistivity from 1.35 × 10 10 to 7.26 × 10 3 Ω sq −1 . The sensitivity of the sensor with the FDM‐printed CNT/TPU dielectric layer microstructure is 0.04034 kPa −1 (0–20 kPa). The prepared CNT/TPU sensors have the advantages of wide detection range (0–800 kPa), a rapid response time (60 ms), and good repeatability, and have potential applications in detecting physical pressure, human motion, and human‐computer interaction. In conclusion, the CNT/TPU composite prepared in this study increases the types of suitable materials for FDM and expands the application potential of FDM. Abstract : CNT/TPU filaments for the FDM process are prepared to improve the mechanical properties and add functionalities to the FDM‐printed parts, such as electrical conductivity and capacitive sensing performance, which increases the types of suitable materials for FDM and extends the application potential of FDM.